Perbandingan Critical Thinking Skill Mata Pelajaran Ekonomi dengan Menggunakan Model Pembelajaran TTA dan AIR - Azka Nahdhiana; Pujiati Pujiati; Rahmah Dianti Putri; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2019)
The objective of this research was to find out the comparison of critical thinking skill which used time token arends and auditory intellectually repetition (AIR). This research using experimental experience. The population of this research was XI grade as the main samples which were taken by random sampling. The hypothesis testing of this research was analysed by using two independent samples t-test formula and N-Gain. The result of the data analysis showed that there was a difference of critical thinking skill between the students who were taught by time token arends and students who were taught by AIR in economic subject. The statement supported by the result of hypothesis testing of 2 methods which could be assumed that AIR was more affective to improve students’ critical thinking instead of time token arends. Tujuan penelitian ini untuk mengetahui perbedaan critical thinking skill yang menggunakan model pembelajaran time token arends dan model pembelajaran auditory, intellectually, repetition (AIR). Metode yang di gunakan dalam penelitian ini adalah metode eksperimen dengan pendekatan komparatif. Populasi dalam penelitian ini adalah seluruh kelas XI dengan jumlah sampel sama diambil dengan teknik sampel jenuh. Pengujian hipotesis menggunakan rumus t-test dua sampel independen dan N-Gain. Hasil analisis data menunjukkan ada perbedaan critical thinking skill antara siswa yang diajarkan dengan model pembelajaran time token arends dibandingkan dengan siswa yang diajarkan dengan model pembelajaran AIR pada mata pelajaran ekonomi. Diperkuat dengan hasil pengujian hipotesis 2 yaitu model pembelajaran AIR lebih efektif untuk meningkatkan critical thinking skill siswa dibandingkan dengan model pembelajaran time token arends.Kata kunci : Auditory Intellectually Repetition (AIR), Critical Thinking Skill, Time Token Arends